Hydro Magnetic Effects on the Flow of Couple Stress Fluid through an Extended Porous Channel. - Bahiru, Zelalem Yidres; Ayano, Mekonnen Shiferaw; -, Taddesse Abdi; -, Ahmed Mohammed (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
This work examine hall and ion-slip effects on the steady state flow of an incompressible and electrically conducting couple stress fluid through an extended porous channel with walls suction and injection. Solutions have been made numerically for the constitutive equations governing the steady state flow of an incompressible and electrically conducting couple stress fluid through a porous channel under the influence of uniform applied magnetic field assuming uniform suction at the upper plate and uniform injection at the lower plate by considering current distribution across the porous channel and the corresponding effect. The obtained magneto hydro dynamic (MHD) momentum equation governing the flow is non-linear, coupled system of higher order differential equation and solved numerically using the so called Quasi-Linearization (Q-L) technique. Furthermore variations of shearing stress and velocity profiles around the extended porous channel with respect to couple stress fluid parameter, hall parameter; ion-slip parameter, suction Reynolds and Hartmann numbers have all been well calculated. Eventually, the variations and relationships of these dimensionless parameters on the magneto hydro dynamic (MHD) flow have been depicted graphically. For computational verification of relationships of parameters we used visual FORTRAN version 95. Key words: - Steady Hydro Magnetic Flow, Magneto-Couple Stress Fluid, Quasi-Linearization, Suction, Injection, Hall and Ion-slip Effects.